Music and movement pedagogy in basic education: a systematic review - del Barrio, Luis; Arús, Mª Eugènia (Frontiers in Education, 2024)
The use of movement in music education addresses the most natural way to express and represent music itself through body. It belongs to the history of pedagogy in music education and empirical research from the 1970’s. For this study, we conducted a systematic review of works that link music and movement pedagogy, from early childhood to secondary education, to establish a revision framework of the existing literature as a reference to advance in the field of pedagogy and music education research. We analysed 29 articles found in the Scopus database from 2013-2023. The results are presented in a PRISMA 2020 Flow Diagram and can be categorised into two emerging areas of intervention: 1) Music and Movement Education. 2) Teaching with Music and Movement in Special Education. Research findings are analysed and presented, and their contributions to education and teaching implications are discussed. Music education and movement pedagogy fosters correlative physical, cognitive and emotional development, and promotes education for all students as an inclusive musical pedagogical approach.